2002
DOI: 10.1007/s11746-002-0449-y
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll breakdown by gamma irradiation in a model system containing linoleic acid

Abstract: The possible breakdown of chlorophyll by irradiation was investigated. Chlorophyll b standard (3 ppm) was added to a methanol solution containing 1% linoleic acid. Irradiation up to 20 kGy was performed with or without N 2 -bubbling, and nonirradiated control was also prepared. Residual chlorophyll b content was analyzed by HPLC and UV-visible spectra after irradiation, and color was measured during 6 h of light exposure (3,300 lux, light intensity) to induce photooxidation. The added chlorophyll b was destroy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 17 publications
3
13
0
Order By: Relevance
“…This is probably due to a disturbance in chlorophyll b biosynthesis or degradation of its precursors as a result of irradiation (Saha et al, 2010). Current findings were also supported by Byun et al (2002) who discovered the destruction of chlorophyll b by irradiation at 20 kGy.…”
Section: Chlorophyll Contentsupporting
confidence: 66%
“…This is probably due to a disturbance in chlorophyll b biosynthesis or degradation of its precursors as a result of irradiation (Saha et al, 2010). Current findings were also supported by Byun et al (2002) who discovered the destruction of chlorophyll b by irradiation at 20 kGy.…”
Section: Chlorophyll Contentsupporting
confidence: 66%
“…Furthermore, Son et al (2001) reported that irradiation can improve the color of natural materials to brighter and transparent such as green tea leaf extract without any changes in its functions. The series of studies using chlorophyll in oil (Byun et al, 2002); persimmon (Disopyros kaki L. folium) leaf and licorice (Glycyrrhiza uralensis Fischer) root (Jo et al, 2003), Lonicera japonica and Curcuma aromatica extracts (Kim et al, 2006) have supported the finding and has been applied in industry. An et al (2005) also reported that irradiation of the polyphenols isolated from green tea leaf up to 40 kGy did not change the physiological activities for human skin.…”
Section: Introductionmentioning
confidence: 76%
“…Leaf chlorophyll content is a good indicator of photosynthesis, mutation, and stress, and the eff ect of gamma radiation on chlorophyll content has been investigated (Byun et al 2002, Ling et al 2008. In concordance with our results (Figure 3A), several studies have previously reported that photosynthetic pigments are reduced by gamma-irradiation.…”
Section: Discussionmentioning
confidence: 99%